Chemical Characteristics and Source Apportionment of Summer Precipitation at the Mount Wutai, Shanxi Province - Jin Zehui; Zhou Qing; Wang Gaofang; Zhang Lei; Wang Zizhong; Zhang Long; Meng Jie; Huang Lei; Tian Conghai (应用气象学报)
In order to reveal chemical characteristics of precipitation at the Mount Wutai, based on continuous precipitation observation data from 20 events at the Mount Wutai in Shanxi Province from June to August in 2022. pH value, conductivity, composition and sources of major water-soluble ions in precipitation are analyzed using methods such as the enrichment factor method, positive matrix factorization model (PMF) and Hybrid Single Particle Lagrangian Integrated Trajectory Model (HYSPLIT). Results indicate that the weighted average pH and conductivity values of rainfall during the summer at Mount Wutai are 6.16 and 15.51 μS·cm-1, respectively. It suggests that the acid rain pollution is not severe, and the precipitation composition is relatively clean. The ranking of the mass concentrations of major ions in precipitation, from highest to lowest, is as follows: SO42-, NO3-, NH4+, Ca2+, K+, Na+, Cl-, Mg2+ and F-. Percentages of NH4+ and Ca2+ in the total ion mass concentration are 20% and 7%, while percentages of SO42- and NO3- in the total ion mass concentration are 33% and 27%. Different ions exhibit different characteristics with rainfall under the influence of upstream air masses. Overall, compared with other high-altitude stations, it presents typical precipitation chemical characteristics of inland high-altitude stations. In the case of 0.01 significant level, the highest correlation coefficient is observed between SO42- and NO3- due to their similar chemical properties and related precursor emission characteristics, the correlation coefficient between K+ and Na+ is 0.899, the correlation coefficient between Mg2+and Ca2+ is 0.827, and the correlation coefficient between Mg2+ and Na+ is 0.778. K+ and Mg2+ are enriched relative to the ocean, and Cl- is diluted relative to the ocean and crust. Traffic activities and dust contribute significantly to levels of Cl- and Ca2+. Agricultural practices, such as fertilization, result in elevated concentrations of F- and NH4+. Additionally, biomass combustion is associated with higher levels of K+. SO42- and nitrate (NO3-) primarily originate from fossil fuel combustion and automobile exhaust emissions. Additionally, summer precipitation at the Mount Wutai is significantly influenced by the southerly air mass. The precipitation from the southern air mass (excluding NH4+) is greater than that from the northern air mass. The total ion concentration in the southern air mass is 1.3 times greater than that in the northern air mass.